2014
DOI: 10.1155/2014/869307
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Its Relationship with Metabolic Markers in Persons with Obesity and Type 2 Diabetes in the UAE: A Cross-Sectional Study

Abstract: Aim. To report vitamin D status and its impact on metabolic parameters in people in the United Arab Emirates with obesity and type 2 diabetes (T2D). Methodology. This cross-sectional study included 309 individuals with obesity and T2D who were randomly selected based on study criteria. Serum concentrations of 25-hydroxy vitamin D (s-25(OH)D), calcium, phosphorus, parathyroid hormone, alkaline phosphatase, glycemic profile, and cardiometabolic parameters were assessed in fasting blood samples, and anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
4
32
0
Order By: Relevance
“…Demographic factors have long been a source of interest in the epidemiology of vitamin D deficiency [19, 21, 22]. Interestingly, our study found that vitamin D levels were significantly lower in Emirati as compared to non-Emirati adults.…”
Section: Discussionmentioning
confidence: 54%
“…Demographic factors have long been a source of interest in the epidemiology of vitamin D deficiency [19, 21, 22]. Interestingly, our study found that vitamin D levels were significantly lower in Emirati as compared to non-Emirati adults.…”
Section: Discussionmentioning
confidence: 54%
“…Likewise, Bani-Issa and colleagues (2017) have observed obesity and T2DM to be bivariate correlators (which were independent of each other) with vitamin D deficiency in Emiratis (12). In addition, Sadiya et al (2014) documented in their cross-sectional study which was performed in UAE the coexistence of these three cofactors – obesity, vitamin D deficiency and T2DM (54). Therefore, the present study recommends early screening and detection of T2DM in the presence of obesity and vitamin D deficiency, with rapid and aggressive corrections of these two predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, more research is focusing on the understanding of the relationship between vitamin D status and obesity [8]. Studies in the Middle East assessing this relationship are limited [10][11][12], even though many countries in the Middle East reported high prevalence rates of low vitamin D status and obesity [5,9,13]. Gannage et al, 2010 showed that 25(OH)D was inversely correlated with BMI (r = − 0.18; p < 0.01) and WC (r = − 0.19; p < 0.01) among 381 Lebanese non-obese university students.…”
Section: Introductionmentioning
confidence: 99%
“…One cross-sectional study among 309 obese diabetic adults (age range: 30-60 years) in UAE showed that the prevalence of 25(OH)D < 50 nmol/L was 83.2%. Furthermore, serum 25(OH)D correlated negatively with body mass index (BMI) (r = − 0.15, p < 0.05), waist circumference (WC) (r = − 0.17, p < 0.05), and fat mass (r = − 0.16, p < 0.05) [10]. The results of this study cannot be generalized to the general population, as the study participants were diabetic and obese, and the relationship between vitamin D status and obesity could be altered by diabetes.…”
Section: Introductionmentioning
confidence: 99%